Use of the Extended Parallel Processing Model to Evaluate Culturally Relevant Kernicterus Messages. - Russell, Jessica C.; Smith, Sandi; Novales, Wilma; Massi Lindsey, Lisa L.; Hanson, Joseph (Journal of Pediatric Healthcare, 2013)
Abstract: Introduction: Kernicterus is a serious but easily preventable disease in newborns that is not well-known even by some health care professionals. This study evaluated a parent guide and poster on kernicterus awareness and prevention generated by the Centers for Disease Control and Prevention. The Extended Parallel Processing Model was used as a framework for creating the interview protocol and analyzing the results. Method: In-depth interviews were conducted with four parents and six health care personnel of different ethnicities to evaluate the materials. Content for the parent guide and poster was held constant, but photos were varied according to the ethnicity of the baby (white, African American, or Hispanic) and the language in which the interviews were conducted (English and Spanish). Results: The parent guide was evaluated positively, but reactions to the poster were varied. The consensus was that the poster drew more attention than the pocket guide but lacked sufficient information about what jaundice is or how to treat it, while the pocket guide provided information, especially with regard to efficacy. The Extended Parallel Processing Model claims that when efficacy is equal to or higher than perceived threat, respondents should engage in recommended responses, which was the general finding from these interviews. Discussion: Recommendations for improvements of the materials are presented. The focus on different ethnicities in the materials was perceived as unnecessary and potentially counter-productive. Both parents and health care professionals mentioned the lack of information regarding treatment. Providing information on the length and effectiveness of treatment for jaundice and kernicterus might increase efficacy in averting the threat in both conditions.